2013
DOI: 10.4081/ni.2013.e23
|View full text |Cite
|
Sign up to set email alerts
|

Urinary dysfunction in women with multiple sclerosis: analysis of 61 patients from Rio de Janeiro, Brazil

Abstract: The aim of the present study is to describe the type and frequency of bladder dysfunction in a series of female patients with multiple sclerosis (MS) from Rio de Janeiro, and analyze the role of the urologist in the multidisciplinary team. A team of urologists and a neurologist from the Hospital da Lagoa, Rio de Janeiro, Brazil, interviewed female patients with MS about illness onset, urologic follow-up since diagnosis, current stage of the disease and current urological symptoms. The interview was followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The results of a study in Brazil showed a weak significant relationship between the duration of the disease and the presence of urinary dysfunction, and the degree of urinary dysfunction increased over the years. [43] In another study, the duration of disease and higher degree of disability only had a significant relationship with higher levels of urinary symptoms in women. [13] The review of data from the American Research Committee on Multiple Sclerosis (NARCOMS) showed that, with an increase in the duration of disease, the severity and prevalence of LUTS increased, so that on average 35-39% of patients 5-6 years after the onset of the disease, and in contrast, 64% of patients with a 17.1 year history of disease reported LUTS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of a study in Brazil showed a weak significant relationship between the duration of the disease and the presence of urinary dysfunction, and the degree of urinary dysfunction increased over the years. [43] In another study, the duration of disease and higher degree of disability only had a significant relationship with higher levels of urinary symptoms in women. [13] The review of data from the American Research Committee on Multiple Sclerosis (NARCOMS) showed that, with an increase in the duration of disease, the severity and prevalence of LUTS increased, so that on average 35-39% of patients 5-6 years after the onset of the disease, and in contrast, 64% of patients with a 17.1 year history of disease reported LUTS.…”
Section: Discussionmentioning
confidence: 97%
“…[44] The current study revealed that the prevalence of LUTS was higher in patients with CIS; however, the prevalence of mixed LUTS in patients with progressive MS was higher in comparison to patients with MS with RRMS and CIS, and the difference was statistically significant. De Almedia reported prevalence rates of 63.5% and 100%, respectively, among patients with RRMS and primary progressive MS. [43] Moreover, a study by Wang et al showed the lowest OBASS score in patients with CIS. [23] In the present study, patients with MS and LUTS symptoms compared to LUTS-free patients had lower QOL scores in all dimensions except for health changes and there was a significant difference in the combined physical and mental health dimensions of QOL between the two groups with and without LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study in Brazil showed a weak significant relationship between the duration of the disease and the presence of urinary dysfunction, and the degree of urinary dysfunction increased over the years. [48] In another study, the duration of disease and higher degree of disability only had a significant relationship with higher levels of urinary symptoms in women. [14] The review of data from the American Research Committee on Multiple Sclerosis (NARCOMS) showed that, with an increase in the duration of disease, the severity and prevalence of LUTS increased, so that on average 35-39% of patients 5-6 years after the onset of the disease, and in contrast, 64% of patients with a 17.1 year history of disease reported LUTS.…”
Section: Discussionmentioning
confidence: 97%
“…[49] The current study revealed that the prevalence of LUTS was higher in patients with CIS; however, the prevalence of mixed LUTS in patients with progressive MS was higher in comparison to patients with MS with RRMS and CIS, and the difference was statistically significant. De Almedia reported prevalence rates of 63.5% and 100%, respectively, among patients with RRMS and primary progressive MS. [48] Moreover, a study by Wang et al showed the lowest OBASS score in patients with CIS. [29] In the present study, patients with MS and LUTS symptoms compared to LUTS-free patients had lower QOL scores in all dimensions except for health changes and there was a significant difference in the combined physical and mental health dimensions of QOL between the two groups with and without LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we were unable to complete blood draws in some subjects, and it appeared that hypo-hydration could have been a factor. Although we did not determine whether participants had bladder problems, about 80 to 100% of people with progressive MS have bladder insufficiency [101,102]. Future trials should consider the issue of hydration during exercise.…”
Section: Limitationsmentioning
confidence: 88%